Duodenal Adenocarcinoma: Profile and Predictors of Survival Outcomes. Issue 11 (November 2015) - Oyasiji, Tolutope; Alosi, Julie; Tan, Wei; Wilfong, Chandler; Wilkinson, Neal
Duodenal adenocarcinoma is rare. We aimed to evaluate survival outcome and prognostic factors for survival in patients with duodenal adenocarcinoma in recent years, marked by advancement in chemotherapy for gastrointestinal cancers. All patients treated for duodenal adenocarcinoma at our institution between January 2000 and July 2013 were reviewed. Thirty-nine patients were identified: 27 operative patients [21(53.8%) curative and 6 (15.4%) palliative operations] and 12 nonoperative patients [primary systemic chemotherapy, 4 (10.3%), palliative radiotherapy, 1 (2.6%), and no treatment, 7 (17.9%)]. Curative resections included 13 pancreaticoduodenectomies and eight segmental resections. Median overall survival (OS) for entire cohort was 14.4 months. Median OS and one-, three-, and five-year OS were operative group (41.4 months; 79.1%, 50.6%, and 10.6%, respectively); nonoperative group (7.4 months; 25.0%, 8.3%, and 0%, respectively); curative surgery (45.4 months; 92.9%, 62.5%, and 16.7%, respectively) and palliative surgery (5.4 months; 33.3%, 16.7%, and 0%, respectively). Female gender ( P = 0.04), curative resection ( P = 0.03), nodal metastasis ( P = 0.047) and advanced T stage ( P = 0.047) were predictive of OS. Two factors were independently predictive of OS—female gender and curative resection. Overall survival still hinges on curative resection. This favors early detection. Adjuvant treatment modalities such as chemotherapy and radiation require further investigation.